Teachers’ Perceptions of Co-curricular P5 Implementation in Physical Education: A Qualitative Study at SMP Muhammadiyah 9 Bojonegoro - Yuni Asih; Budiono Budiono; Ria Arista Asih (IKIP PGRI Bojonegoro, 2026)
This study explores PJOK teachers’ perceptions of implementing the Pancasila Student Profile Strengthening Project (P5) as a co-curricular program and identifies strategies for integrating the eight graduate profile dimensions. Conducted at SMP Muhammadiyah 9 Bojonegoro, the research employed a qualitative narrative inquiry through interviews, observations, and documentation. Data were analyzed using thematic matrices to reveal patterns of perception and strategy. Findings show that teachers’ perceptions evolved positively, influenced by intrinsic motivation, emotions, and institutional support. Strategies included structured planning, project-based learning, cross-subject collaboration, and authentic evaluation. Activities such as creative gymnastics, traditional games, and health education enhanced physical fitness while instilling values of cooperation, discipline, and independence. The study concludes that PJOK plays a strategic role in embedding Pancasila values through P5, with implications for policy reinforcement, continuous training, and adequate facilities.